Antioxidant Potential of Selected Wild Edible Leafy Vegetables of Sikkim Himalayan Region: Effects of Cooking Methods and Gastrointestinal Digestion on Activity - Sharma, Swati; Padhi, Srichandan; Kumari, Megha; Patnaik, Srinivas; Sahoo, Dinabandhu (Frontiers in Nutrition, 2022)
Green leafy vegetables or GLVs are one of the main attractions in the local vegetable market and are widely consumed as the main course and side dish in the Sikkim Himalayan region (SHR). This study evaluated the total phenolic (TPC) and flavonoid contents (TFC) and antioxidant potential in different extracts such as methanolic (MeOH), ethyl acetate (EtOAC), and hexane extracts of selected GLVs followed by changes in the antioxidant activity on cooking and stimulated gastrointestinal (GI) digestion. The MeOH extracts of Urtica dioica L. (Sisnu), Nasturtium officinale W. T. Aiton (Simrayo), Diplazium esculentum Retz. Sw. (Ningro), and Chenopodium album L. (Bethu) were estimated to have higher TPC [22.73–45.84 μg gallic acid equivalent (GAE)/mg of extract]. In contrast, the plant extracts prepared using EtOAC (except for N. officinale, where TFC was found to be higher in hexane extract) were found to contain higher TFC (3.42–14.86 μg quercetin equivalent (QE)/mg of extract). The MeOH extracts also exhibited higher 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity (9.55–18.67 μg ascorbic acid equivalent (AAE)/mg of extract), total antioxidant activity (TAA) (0.27–0.32 mg AAE/mg of extract), and reducing power potential (RPP) (1.6–9.9 μg AAE/mg of extract). Among the test MeOH extracts, U. dioica demonstrated relatively higher antioxidant activities and was selected for cooking experiments followed by simulated GI digestion. The findings revealed that the loss of antioxidant activity was minimal in steam-cooked leaves (3.5% in 40 min) as compared to the boiled ones (18% in 10 min). The simulated GI (simulated salivary, gastric, and intestinal) digestion performed on raw, steam cooked, and boiled U. dioica leaves showed substantial enhancement of antioxidant properties (by 64.63%) through steam cooking in comparison to the raw leaves. Overall the study concludes that higher antioxidant properties can be achieved on the consumption of steam-cooked U. dioica leaves.